ANALISIS KEAKTIFAN SISWA DALAM PEMBELAJARAN IPAS BERBANTUAN KAHOOT MATERI KABUPATEN TEMPAT TINGGALKU - Wulandari, Firda Eka Ayu; Asriyanti, Frita Devi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student engagement is a key aspect of the learning process because it reflects students’ involvement during classroom activities. Preliminary research findings in third-grade classes at SDN I Jepun indicate that student engagement in learning the “My Home County” curriculum topic is still suboptimal. This study aims to describe and analyze third-grade students’ engagement in using Kahoot during IPAS lessons on the “My Home District” topic at SDN I Jepun in Tulungagung Regency. This study employs a qualitative approach using a descriptive research design. The research subjects consisted of the third-grade teacher and 20 third-grade students at SDN I Jepun. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions. Data validity was tested using source triangulation and methodological triangulation. The research results showed that student engagement was 82.88%, while interviews with teachers and students revealed that most students were actively engaged throughout the learning process. Student engagement was evident through their attention to the lesson, their willingness to answer questions, their ability to express opinions or ask questions, and their active participation in Kahoot quizzes. The use of Kahoot made students more focused, enthusiastic, and motivated to participate in the lesson. Thus, the use of Kahoot supported the creation of interactive learning and encouraged student engagement in IPAS lessons.